Legal System of Community Participation in Environmentally Friendly Power Plants: A Socio-Legal Study of Micro-Hydro Projects in Central Java - Triana, Nita; Mukhtar, Naqiyah; MD Rasip, Osman; Ramadhan, Hafizh Faikar Agung; Monk, Lincoln James Faikar (Unissula, 2025)
Energy management is closely linked to environmental concerns and community involvement. However, in electrical energy regulations, community participation is frequently overlooked, with the community treated solely as a consumer. This study examines the legal system for community participation in environmentally friendly micro-hydro power plants. The research method used was qualitative, with a socio-legal approach. Data was collected through observation and in-depth interviews with purposefully chosen informants. The findings show that the legal system, in the form of legal substance, such as management rules and legal structures, is implemented in a participatory manner by the residents of Karangtengah and Lebakbarang villages. Community participation is critical to the success of the two villages' micro-hydro power projects, which earned them the provincial award for the best management of micro-hydro projects in Central Java. Community participation in this project is strong because the community has a legal culture characterized by cooperation, environmental friendliness, deliberation, and family values. Based on the level of participation, community involvement in the micro-hydro project is at the highest level, namely partnership, delegation of authority, and citizen control.